表層型ガスハイドレート賦存海底・湖底地盤から採取した堆積土の土質特性－間隙水溶存ガスの気泡化に伴う堆積土の試料乱れ評価－ - 山下, 聡; 出羽, 寛信; 八久保, 晶弘; 南, 尚嗣; 片岡, 沙都紀; 川口, 貴之; 坂上, 寛敏; 高橋, 信夫; 庄子, 仁 (Japanese Geotechnical Journal, 2012)
表層型ガスハイドレートが存在しているオホーツク海サハリン島沖およびロシア・バイカル湖において，海底・湖底表層地盤から堆積土を採取した。採取した堆積土に対して，調査船上で小型のベーンせん断試験とコーン貫入試験を行い堆積土の力学特性を調べた。また，試料引き上げ時の間隙水圧減少により，溶存ガスが気泡化し試料に乱れが生じることから，ガス濃度と強度との関係についても調べた。さらに，試料採取から室内試験に至るまでの応力条件を再現した実験を行った。その結果，間隙水中の溶存ガスの濃度が高いほど，船上試験においても再現実験においても強度低下が大きくなる傾向にあった。また，溶存ガスの気泡化により乱れた試料からも，乱れの影響のない強度をある程度推定可能であることも示された。 Core samplings were conducted in offshore Sakhalin Island, Sea of Okhotsk, and in Lake Baikal, Russia, where shallow gas hydrates existed. To examine the mechanical properties of sea and lake bottom sediments, the handy vane shear and cone penetration tests were performed for the core samples on board. To evaluate the sample disturbance due to the exsolution of dissolved gas during sampling, the relations between the concentration of dissolved gas in the pore water and the strength were also examined. Moreover, laboratory tests which simulate the stress relief from bringing the samples to the sea or lake surface were also performed. Test results showed that the strength of soils become lower with the increase in degree of gas saturation on both on-board and laboratory tests. It was also showed that the in-situ strength can be estimated roughly from the disturbed sample. journal article